Chiral Capillary Electrophoresis in Current Pharmaceutical and Biomedical Analysis - Peter Mikus (IntechOpen, 2012)
The scientific monograph by the author Peter Mikus entitled ""Chiral Capillary Electrophoresis in Current Pharmaceutical and Biomedical Analysis"" provides a comprehensive view on the advanced capillary electrophoresis techniques aimed to current chiral bioanalysis. The advances in the chiral electrophoresis analytical approaches are divided and theoretically described in three sections involving (i) advanced chiral separations for the optimization of chiral resolution (separation mechanisms; electrophoresis techniques in capillary and microchip format; electrophoretic modes such as ITP, CZE/EKC, CEC; chiral additives / pseudophases / phases), (ii) advanced sample preparation for the on-line preconcentration, sample clean-up and analyte derivatization (implementation of electrophoretic effects such as stacking; non-electrophoretic effects such as SPE, chromatography, dialysis; combinations of these effects; multidimensional CE systems; instrumental schemes), (iii) advanced combinations of detection and electrophoresis for the optimization in qualitative and quantitative evaluation (the most important universal as well as selective detection approaches such as absorption and fluorescence spectrophotometry, electrochemical detection, mass spectrometry vs. (i) and/or (ii)). Real analytical potential (benefits and limitations) of these advanced analytical approaches is emphasized by selected performance parameters of the methods and illustrated by many current practical applications including chiral analyses of drugs, their (bio)degradation products and biomarkers in pharmaceutical and biological matrices. The author wishes the readers many inspirations in the creation of new innovative approaches in the field of advanced chiral electrophoresis techniques with the aim to overcome capabilities of the current analytical techniques.
English
Keywords: Toxicology and Pharmaceutical Science; Pharmaceutical Science; Pharmacology; Pharmaceutical Chemistry; Health Sciences